2020
DOI: 10.1002/jmv.25790
|View full text |Cite
|
Sign up to set email alerts
|

Association of MCP‐1 promotor polymorphism with disease severity of Crimean‐Congo hemorrhagic fever

Abstract: Crimean‐Congo hemorrhagic fever (CCHF) is a thick‐borne viral zoonotic disease. The pathogenesis and the reasons why cases have a mild or severe course in CCHF have not yet been explained. In this study, we investigated the relationship between promoter ‐2518 A/G single‐nucleotide polymorphism (SNP) of the MCP‐1 gene and the clinical course of CCHF. The MCP‐1‐2518 A/G SNP (rs1024611) frequency was examined in 128 virologically/serologically confirmed CCHF patients and 181 healthy controls by using the PCR‐RFLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Patients were divided into mild/moderate and severe on the basis of clinical severity. The defined criteria for patients were the presence of at least one; leukocyte count ≥10,000/mm 3 , thrombocyte count ≤20,000/mm 3 , aspartate aminotransferase (AST) ≥200 IU/L, alanine aminotransferase (ALT) ≥150 IU/L, activated partial thromboplastin time (aPTT) ≥60 sec, or fibrinogen ≤110 µg/dl in the first 5 days after onset of clinical symptoms as a severe case and absence of any of these as a mild/moderate case (10). Thirty-eight healthy volunteers were enrolled as the control group.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…Patients were divided into mild/moderate and severe on the basis of clinical severity. The defined criteria for patients were the presence of at least one; leukocyte count ≥10,000/mm 3 , thrombocyte count ≤20,000/mm 3 , aspartate aminotransferase (AST) ≥200 IU/L, alanine aminotransferase (ALT) ≥150 IU/L, activated partial thromboplastin time (aPTT) ≥60 sec, or fibrinogen ≤110 µg/dl in the first 5 days after onset of clinical symptoms as a severe case and absence of any of these as a mild/moderate case (10). Thirty-eight healthy volunteers were enrolled as the control group.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…The host genetic background plays a very important role in the pathogenesis and eventual outcome of all kinds of diseases 3 . It has been reported that some genes could affect the pathogenesis and outcome of infectious diseases 4–6 . Interleukin‐32 (IL‐32), which is a multifunctional inflammatory cytokine, is related to the pathogenesis of many diseases, such as inflammatory bowel disease, 7 HIV infection, 8 and rheumatoid arthritis 9 …”
Section: Introductionmentioning
confidence: 99%
“…3 It has been reported that some genes could affect the pathogenesis and outcome of infectious diseases. [4][5][6] Interleukin-32 (IL-32), which is a multifunctional inflammatory cytokine, is related to the pathogenesis of many diseases, such as inflammatory bowel disease, 7 HIV infection, 8 and rheumatoid arthritis. 9 The IL-32 gene, located on chromosome 16 p 13.3, contains 8 exons and 6 isoforms: IL-32α, β, γ, δ, ε and ζ.…”
Section: Introductionmentioning
confidence: 99%